Integrated morphophysiological, transcriptomic, and metabolomic data uncover the molecular mechanism of environmental adaptation of Zanthoxylum armatum with different latitudinal gradients - Guo, Yuan; Fu, Xueqian; Sun, Chong; Deng, Yifei; Liu, Han; Tong, Long; Kuang, Mi; Tang, Ning; Yang, Wenying; Liu, Xia; Chen, Zexiong (Frontiers in Plant Science, 2025)
IntroductionLeaves are sensitive to environmental changes and directly reflect the degree of environmental impact on plants and their ability to adapt to the environment, making it crucial to understand the genetic mechanisms underlying leaf variation. Zanthoxylum armatum is a widely distributed and economically important forest species in China that shows remarkable regional adaptability. However, adaptive differences under diverse environmental conditions and their molecular mechanisms have not been systematically studied.MethodsPlant materials of Z. armatum from three regions (Shandong, Chongqing, and Yunnan) representing different latitudinal backgrounds were cultivated under uniform conditions. Morphological, physiological, and biochemical traits were measured, including stomatal density, nutrient content, antioxidant capacity, and chlorophyll level. Transcriptomic and metabolomic profiling were conducted using RNA-seq and UPLC-MS/MS, respectively. Differential expression and enrichment analyses (GO, KEGG), gene family screening, and correlation analyses were used to identify key genes and metabolites. Selected gene expression patterns were further validated using qRT-PCR.ResultsUnder common garden conditions, the three Z. armatum populations retained distinct physiological and molecular profiles. SD, CQ, and YN groups showed respective advantages in antioxidant activity, nutrient accumulation, and chlorophyll content. Integrated transcriptomic and metabolomic analyses identified seven resistance-related and two photosynthesis-associated genes, significantly correlated with physiological traits. Ninety-two differential metabolites were detected, including two enriched in phenylpropanoid and flavonoid pathways. The YN group exhibited more coordinated gene expression across key metabolic pathways, indicating greater potential for metabolic flux. These results highlight molecular features underlying population-level variation under common garden.DiscussionThrough multi-level comprehensive research, a new perspective has been provided for revealing the molecular regulatory network of the environmental adaptability of Z. armatum. In the future, we can use plant genome editing tools to target these genes as the bases and transform them into Z. armatum varieties with multiple resistance qualities, thereby contributing to scientific research and commercial Sichuan pepper cultivation.